2021
DOI: 10.1002/inf2.12269
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new two‐dimensional titanium carbonitride Ti2C0.5N0.5TxMXene and its performance as an electrode material for sodium‐ion battery

Abstract: Two‐dimensional (2D) layered transition metal carbides/nitrides, called MXenes, are attractive alternative electrode materials for electrochemical energy storage. Owing to their metallic electrical conductivity and low ion diffusion barrier, MXenes are promising anode materials for sodium‐ion batteries (SIBs). Herein, we report on a new 2D carbonitride MXene, viz., Ti2C0.5N0.5Tx (Tx stands for surface terminations), and the only second carbonitride after Ti3CNTx so far. A new type of in situ HF (HCl/KF) etchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 69 publications
1
35
0
Order By: Relevance
“…30 The introduction of nitrogen generally increases the sodium capacity on these Ti-containing MXenes. 31,32 A high specific capacity of 182 mA h g −1 was realized for Ti 2 C 0.5 N 0.5 T x , which is the highest capacity of all reported multilayer MXenes. 31 The introduction of sulphur also enhances the storage capacity.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…30 The introduction of nitrogen generally increases the sodium capacity on these Ti-containing MXenes. 31,32 A high specific capacity of 182 mA h g −1 was realized for Ti 2 C 0.5 N 0.5 T x , which is the highest capacity of all reported multilayer MXenes. 31 The introduction of sulphur also enhances the storage capacity.…”
Section: Introductionmentioning
confidence: 86%
“…31,32 A high specific capacity of 182 mA h g −1 was realized for Ti 2 C 0.5 N 0.5 T x , which is the highest capacity of all reported multilayer MXenes. 31 The introduction of sulphur also enhances the storage capacity. 33,34 In particular, a high capacity of 550 mA h g −1 at 0.1 A g −1 was reported in sulphur intercalated Ti 3 C 2 T x .…”
Section: Introductionmentioning
confidence: 86%
“…1b). 17,25,37–40 The difficulty in synthesizing non-carbide MXenes could be attributed to two significant factors. Firstly, Ti n +1 N n has less cohesive energy than Ti n +1 C n ; thus, the nitride MXene structures have lower stability and dissolve easily in the hydrofluoric acid (HF) solution, the etchant widely used to produce carbide MXenes from their MAX phases.…”
Section: Non-carbide Mxenesmentioning
confidence: 99%
“…Liang and co-workers reported the synthesis of Ti 2 C 0.5 N 0.5 T x MXene from its MAX phase Ti 2 AlC 0.5 N 0.5 using the KF-HCl ( in situ HF) etching approach similar to that of the LiF–HCl mild etching method. 17 Until now, Ti 2 C 0.5 N 0.5 T x and Ti 3 CNT x are the only synthesized carbonitride MXenes. An absence in the MXene peaks and increased weight loss in the material indicated that HF etching is not the optimum method to synthesize Ti 2 C 0.5 N 0.5 T x MXene.…”
Section: Carbonitride Mxenesmentioning
confidence: 99%
See 1 more Smart Citation